PENGARUH GAYA KEPEMIMPINAN DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KEPUASAN KERJA (Studi pada Kantor Dinas Kesehatan Kabupaten Rembang) (Jurnal Mahasiswa Pasca Sarjana, 2013)
Good leadershipstyleandorganizational commitmentis high inanorganizationcanaffectthe progressoganization. Research purposestorevealthe  relationshipbetweenleadership style, organizational commitmentandjob satisfactionon employee performanceatthe District Health OfficeRembang.The study populationwasall employees ofthe District Health OfficeRembang, amounting to 90peopleusingcensustechniques. The data was collectedby means ofquestionnaires. The independent variableis theleadership style, organizational commitment, andjob satisfactionis amediatingvariable. The dependent variableisthe performance. Multiple regressionanalysisandpath analysisis usedtodetermine the effect ofindependent variableson the dependent variable, as well as themediatingvariable.Results of this studyindicatethatleadership style, organizational commitment and job satisfactionarepositivelyandsignificantlyimpacton performance. Whilejob satisfactiondid notmediate theeffect ofleadership styleandorganizational commitmentto performance.Keywords: Leadership Style, OrganizationalCommitment, Job Satisfaction andPerformance